The Beliefs about Paranoia Scale: Confirmatory factor analysis and tests of a metacognitive model of paranoia in a clinical sample. (February 2017) - Murphy, Elizabeth K.; Tully, Sarah; Pyle, Melissa; Gumley, Andrew I.; Kingdon, David; Schwannauer, Matthias; Turkington, Douglas; Morrison, Anthony P.
Abstract: This study aimed to confirm the factor structure of the Beliefs about Paranoia Scale (BaPS), a self-report measure to assess metacognitive beliefs about paranoia, and to test hypotheses of a metacognitive model. We hypothesised that positive and negative beliefs about paranoia would be associated with severity of suspiciousness, and that the co-occurrence of positive and negative beliefs would be associated with increased suspiciousness. A total of 335 patients meeting criteria for a schizophrenia spectrum disorder completed the BaPS, the Positive and Negative Syndromes Scale (PANSS), and the Psychotic Symptom Rating Scales (PSYRATS). Confirmatory factor analysis verified that the three BaPS subscales (negative beliefs about paranoia, paranoia as a survival strategy, and normalizing beliefs) were an adequate fit of the data. Ordinal regression showed that positive beliefs about paranoia as a survival strategy and negative beliefs were both associated with severity of suspiciousness. This was the first study to show that the co-occurrence of positive and negative beliefs was associated with increased suspiciousness. All hypotheses were confirmed, suggesting that a metacognitive approach has utility for the conceptualization of paranoia. Clinical implications suggest a role for metacognitive therapy, including strategies such as detached mindfulness and worry postponement. Highlights: The Beliefs about Paranoia Scale measures metacognitive beliefs about paranoia. Positive beliefs about paranoia were associated with clinical paranoia. Negative beliefs about paranoia were associated with clinical paranoia. The co-occurrence of positive and negative beliefs was associated with paranoia. This supports a metacognitive model of paranoia as a strategy for managing threat.